The effects of an afterschool STEM program on students’ motivation and engagement - Chittum, Jessica R.; Jones, Brett D.; Akalin, Sehmuz; Schram, Asta B. (My University, 2017)
Background: One significant factor in facilitating students’ career intentions and persistence in STEM (science, technology, engineering, and mathematics) fields is targeting their interests and motivation before eighth grade. To reach students at this critical stage, a design-based afterschool STEM program, titled Studio STEM, was implemented to foster motivation and engagement in STEM topics and activities. The purpose of this study is twofold: (a) to investigate how Studio STEM affected students’ beliefs about science and whether these beliefs differed from their peers who did not participate in the program, and (b) to examine a case study of one Studio STEM implementation to investigate elements of the curriculum that motivated students to engage in the program. Results: After completing two Studio STEM programs, participants’ ratings of their values for science and science competence were higher than those of non participants. In addition, the Studio STEM participants’ motivational beliefs about science and intentions to pursue a college degree were more resilient over time than their peers. We also found that students could be motivated in a voluntary afterschool program (Studio STEM) in which they grappled with STEM concepts and activities, and could verbalize specific program elements that motivated them. Conclusions: Through this study, we found that students could be motivated in Studio STEM and that the experience had a positive impact on their perceptions about science as a field. Importantly, Studio STEM appeared to halt the decline in these students’ motivational beliefs about science that typically occurs during the middle school years, indicating that after school programs can be one way to help students maintain their motivation in science. Studying the program features that the students found motivating may help educators to make connections between research and theory, and their classroom instruction to motivate their students.
Keywords: Motivation; STEM education; Afterschool program; Mixed methods research